Evaluación de la capacidad degradadora de Trichoderma sp. y Aspergillus sp. en bagazo de caña de azúcar. - Amaya Lema, Jonathan Naun (2021)
The present research work aims to bibliographically evaluate the degrading capacity of Trichoderma sp. and Aspergillus sp. in sugarcane bagasse, for which a bibliographic review was carried out, in these studies the decomposition speed of sugarcane bagasse by Trichoderma sp, and Aspergillus sp. was compared, and the information obtained from the two genera of fungi. It is realized that each of the fungi has characteristics that make them efficient when decomposing the sugarcane bagasse, and that the degradation efficiency depends on the environment in which they are inoculated in addition to the characteristics of the substrates such as: pH, temperature, organic matter and total organic carbon. An analysis of the enzymatic activity was presented from each study, for the Aspergillus genus the fungus that reached the highest value was A. niger with 0.3 IU / mL in cellulase enzymes, while in the Trichoderma genus the species with the highest enzyme production was T. reesei he presented a value of 0.59 IU / mL. The decomposition time of lignocellulose was found to vary exponentially with respect to the rate of enzyme production. The shortest degradation time of sugarcane bagasse was 5 hours by Trichoderma longibrachiatum. By analyzing the degrading capacity of fungi, the use of lignocellulosic residues to make organic fertilizers or food such as animals can be promoted.